On the Number of Zeroes of Exponential Systems (Journal of Computational Mathematics, 1991)
A system $E:C^n→ C^n$ is said to be an exponential one if its terms are $ae^{im_1Z_1}.… .e^{im_nZ_n}$. This paper proves that for almost every exponential system $E:C^n→ C^n$ with degree $(q_1,…,q_n)$, $E$ has exactly $Π^n_j=1(2q_j)$ zeroes in the domain $D=\{(Z_1,…,Z_n)\in C^n:Z_j=x_j+iy_j,x_j,y_j\in R,0≤ x_j